2007
DOI: 10.1111/j.1365-313x.2007.03331.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed after‐ripening is a discrete developmental pathway associated with specific gene networks in Arabidopsis

Abstract: SummaryAfter-ripening (AR) is a time and environment regulated process occurring in the dry seed, which determines the germination potential of seeds. Both metabolism and perception of the phytohormone abscisic acid (ABA) are important in the initiation and maintenance of dormancy. However, molecular mechanisms that regulate the capacity for dormancy or germination through AR are unknown. To understand the relationship between ABA and AR, we analysed genome expression in Arabidopsis thaliana mutants defective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(204 citation statements)
references
References 39 publications
6
194
1
3
Order By: Relevance
“…Mechanisms regulating after-ripening are not well understood (11,13). Previously, it has been shown that catabolism of ABA in imbibed seeds is an important regulator of germination potential, and that seeds lacking ABA 8Ј-hydroxylase activity exhibit enhanced dormancy (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms regulating after-ripening are not well understood (11,13). Previously, it has been shown that catabolism of ABA in imbibed seeds is an important regulator of germination potential, and that seeds lacking ABA 8Ј-hydroxylase activity exhibit enhanced dormancy (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis seed germination is regulated by intrinsic hormonal pathways and external environmental signals, which influence whether an imbibed seed completes germination or remains dormant (10)(11)(12). Dry Arabidopsis seeds exhibit physiologically non-deep dormancy, and following shedding they go through a period of after-ripening, through which the capacity for dormancy is lost (10,13). The Arabidopsis embryo is surrounded by 2 structures: a single endosperm cell layer and an external, dead testa layer that is maternally derived (11).…”
mentioning
confidence: 99%
“…In this respect, its participation in a ternary complex with C/S bZIPs might partly explain many of numerous pleotropic effects observed in abi3 mutants. Interestingly, transcriptomic data suggest that bZIP53 and bZIP10 expression levels are reduced in mutant abi3-4 developing seeds (Carrera et al, 2008).…”
Section: A Model Of Seed Maturation Gene Expression Triggered By Bzipmentioning
confidence: 99%
“…Mature seeds require a period of after-ripening to overcome dormancy (Carrera et al, 2008). Two-weekold freshly harvested cer9-2 seeds exhibited a higher rate (80%) of dormancy than the wild-type Columbia-0 (Col-0; 16%; Fig.…”
Section: Cer9 Loss Of Function Promotes Seed Dormancymentioning
confidence: 99%